Effect of glass fiber on the properties of expansive soil and its utilization as subgrade reinforcement in pavement applications - Samer Rabab’ah (Case Studies in Construction Materials, 2021)
The purpose of this study is to investigate the use of glass fibers as discrete random reinforcement in expansive subgrade soil to improve its strength for pavement application. The fiber content varied between 0.25 % and 1.0 % by weight of dry soil. A series of free swell, Unconfined Compressive Strength (UCS), Indirect Tensile Strength (ITS), and California Bearing Ratio (CBR) tests were conducted on unreinforced and reinforced expansive soil specimens. In addition, the effect of the inclusion of the fiber on the design and performance of flexible pavement was evaluated using the Mechanistic-Empirical Pavement Design Guide (MEPDG). The test results showed that the inclusion of glass fibers in subgrade soil significantly increases the UCS, ITS, and CBR, and decreases the free swell values. MEPDG analyses showed that the glass fibers could be a suitable reinforcement for the subgrade layer for pavement construction. A significant decrease in pavement thickness can be achieved by the inclusion of glass fibers in subgrade stabilization.